Case Report: Mature Plasmacytoid Dendritic Cell Proliferation Associated With a Lymphoid Neoplasm - Fei, Fei; Liedtke, Michaela; Silva, Oscar (Frontiers in Oncology, 2022)
Mature plasmacytoid dendritic cell proliferations (MPDCPs) are clonal, non-malignant pDC proliferations that have been reported to occur in association with myeloid neoplasms such as CMML, AML (pDC-AML), and rarely MDS or MPNs. Here we report the first case of a MPDCP associated with T-lymphoblastic leukemia (T-ALL), a lymphoid neoplasm. The MPDCP in this case involved ~50% of the bone marrow, was found in nodular aggregates, expressed CD123, CD4, CD303 and lacked CD56 and TCL1 expression. In addition, the MPDCP lacked CD34 and TdT, but showed aberrant expression of CD7, CD5, CD10 and CD13, markers expressed by the abnormal T-lymphoblastic cells. Mutational analysis demonstrated mutations in JAK3, NOTCH1, NRAS, KRAS, DNMT3A and SH2B3, but no mutations in TET2, ASLX1 or ZRSR2. Analysis of the pDC frequency in a separate cohort of T-ALL and control patients demonstrated that bone marrow pDCs are often decreased in T-ALL patients compared to controls. This is the first report of a MPDCP associated with a lymphoid neoplasm and provides further support that MPDCP can arise from a multipotent hematopoietic progenitor with lymphoid and dendritic cell potential.